RAHASIA LULUR ALAMI UNTUK BODY SPA TRADISIONAL DAN MODERN - Neguita Pinem, Igrelatercia; Ardhita Manda Putri, Wisri; C Haq B Junior Harahap, Nabiel; Daniella Br Perangin-angin, Grace; Serepia Samosir , Agnes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Traditional lulur is a scrub made from natural ingredients such as spices, rice, clay, honey, and vegetable oils. It serves various functions, including exfoliating dead skin cells, cleansing pores, brightening and moisturizing the skin, firming the skin, improving blood circulation, as well as providing relaxation and anti-aging effects. The development of lulur from traditional to modern forms has incorporated formulation technology and dermatological science without losing the essence of its natural ingredients, resulting in various innovations such as lulur based on charcoal-clay, guava leaf extract, durian peel waste, pumpkin extract with coconut pulp, purple sweet potato, avocado-olive oil, papaya, matcha, sandalwood-saffron, as well as milk-honey and olive oil-sugar. This book also outlines the correct steps for using lulur according to skin type (dry, oily, combination, sensitive, and normal), while providing warnings regarding potential risks such as allergies, irritation, and side effects due to excessive use or overly strong abrasive ingredients. The aspects of equipment and container sterilization as well as proper storage methods are also discussed in depth to prevent microbial contamination. Overall, this book aims to serve as a practical guide for readers who wish to learn and practice skin care with natural lulur in a safe, effective, and sustainable manner.